(untitled) (Journal of Environmental Bioremediation and Toxicology, 2014)
The increasing use of feather in removing heavy metals from water continues to generate feather wastes contaminated with heavy metals which make it difficult for feather-degrading bacteria to degrade them. In this study, the capacity of Bacillus sp. khayat to grow, produce keratinase and degrade chicken feathers contaminated with various heavy metals, chemicals and surfactants was investigated. The results showed that keratinase activity, feather degradation and the bacterial growth increases with an increase in concentration up to 10 ppm for certain metals, 15 ppm for Cr and Zn and up to 20 ppm for Cu. CaCl2 and Fe2SO4 have negative effect on growth, KA and feather degradation when placed in medium or in cell free crude keratinase except Ca ion which affect crude crude keratinase less. Feather degradation was enhanced at 5 ppm in Pb, Ni, As, Cr and Cu. However, Hg showed decreased feather degradation after 1 ppm. About 90-100 % feather were degraded in the presence of 10 ppm Ni, Ag, Cr, Zn and Co. Ni, Ag, Zn and Cu were the best tolerated metals. Bacillus sp. khayat, with a relatively high tolerance to heavy metals while still maintaining its feather-degrading activities, appears to be a bacterial model for toxic environmental waste.